(untitled) (Povijesni prilozi (Historical Contributions), 2019)
The history of the Roma population on the Croatian area was marked by the periods in which the Roma faced the impact of the repressive and assimilatory policy of the state and local authorities towards them. Th e period of the reign of Maria Theresa and Joseph II was marked by such a policy, as they issued numerous decrees on Roma. The main goal of this policy was to reform the status of the Roma population by ordering them the forced sedentarization, the prohibition of their identity, e.g. their name, the use of their language and customs, doing their traditional professions and so on. As the result of such a policy, the Roma should have become the integrated part of the Habsburg society. The similar enlightened policy toward the Roma was conducted by the other European rulers as well. Th is paper is based on the research of the archival fonds of the Croatian State Archives, as well as the analysis of the relevant literature.